Increased order in single molecule magnets : Masters thesis under the supervision of Associate Professor Gareth J. Rowlands, Chemistry, Institute of Fundamental Sciences, Massey University - Farrow, Zane (Massey University, 2018)
Single Molecule Magnets (SMMs) show promise in advancing computer technology and our understanding of quantum behaviours, however we first have to understand how to successfully synthesize ligand systems that allow them to perform at viable temperatures. As such, my project explored the synthesis of new ligand systems for potential SMMs based on [2.2]paracyclophane and pyrazine. These structures were chosen to be a synthetic backbone for the synthesis of new ligands for potential SMMs formation due to their structural and electronic properties. Attempts were undertaken to form complexes with these ligands and grow crystals suitable for X-ray crystallography. In this project three new ligand systems were synthesized and characterized, one with a [2.2]paracyclophane backbone (L₁) and two containing a pyrazine bridging group (L₂ and L₃). Complexations with a variety of metals were undertaken with all three ligands, unfortunately crystals of sufficient quality for single crystal X-ray diffraction experiments were not obtained. In total 8 new compounds were synthesized and a novel route for the synthesis of 4-(benzylamino)[2.2]PC was developed during this project.
Keywords: Ligands; Molecules; Magnetic properties; Magnetochemistry